Planejamento por modelagem e dinâmica molecular de filtros solares seguros - Passamani, Fabiana (2023)
The use of sunscreens is important in reducing the harmful effects caused by UV radiation. When applied in the personal care routine, the sunscreens ingredients can assume inappropriate destinations, such as cutaneous permeation and bioaccumulation, which may have adverse impacts on human health and the environment. Information on the endocrine disrupting risks of UV filters is not satisfactory, requiring studies that elucidate ligandreceptor recognition. This work sought to employ different computational tools in order to obtain relevant information about the endocrine disrupting activity of these messages. Through Density Functional Theory (DFT) analysis, we sought to predict incorporated property descriptors comprising the reactivity of UV filters. Using the web tool http://endocrinedisruptome.ki.si, it was possible to analyze the probabilities of interaction of nuclear receptors with commercially available UV filters and with natural molecules used in sunscreens, seeking to understand the health risk. A further exploration was performed together with the activating ligand testosterone and the endocrine disruptor Bisphenol-A, analyzing the interaction mechanisms of the stable ligand-receptor complex by molecular docking. The target was the androgen receptor (AR), which in excessive activation can trigger prostatic hyperplasia and cancer. The results show interaction with the AF-2 activation site of AR, similar to the AR-Testosterone complex, with lower docking energy, but close to Bisphenol-A. The molecules also assumed other induction pathways, such as activation of the BF3 region. To understand the magnitude of the interactions, molecular dynamics simulations showed that AR undergoes changes in the presence of Benzophenone-3 and Cinoxate, aiming to achieve stabilization and structural changes in the residues of the activation pocket, by hydrogen bonding and hydrophobic, resulting in the expansion of the receptor similar to testosterone. However, there is a dispersion of surface charges and an increase in solvent accessible surface, with lower hydrophobicity creating an unfavorable condition for affinity compared to testosterone. Finally, it sought through DFT calculations to predict electronic property descriptors including the reactivity of UV filters and their relationship with theoretical sensors. This study elucidates information relevant to the endocrine disruption of UV filters, which can be used in the development of safer sunscreens.